Deep sequencing and transcriptome analyses to identify genes involved in secoiridoid biosynthesis in the Tibetan medicinal plant Swertia mussotii - Liu, Yue (Sci Rep, 2017)
Swertia mussotii Franch. is an important traditional Tibetan medicinal plant with pharmacological properties effective in the treatment of various ailments including hepatitis. Secoiridoids are the major bioactive compounds in S. mussotii. To better understand the secoiridoid biosynthesis pathway, we generated transcriptome sequences from the root, leaf, stem, and flower tissues, and performed de novo sequence assembly, yielding 98,613 unique transcripts with an N50 of 1,085 bp. Putative functions could be assigned to 35,029 transcripts (35.52%) based on BLAST searches against annotation databases including GO and KEGG. The expression profiles of 39 candidate transcripts encoding the key enzymes for secoiridoid biosynthesis were examined in different S. mussotii tissues, validated by qRT-PCR, and compared with the homologous genes from S. japonica, a species in the same family, unveiling the gene expression, regulation, and conservation of the pathway. The examination of the accumulated levels of three bioactive compounds, sweroside, swertiamarin, and gentiopicroside, revealed their considerable variations in different tissues, with no significant correlation with the expression profiles of key genes in the pathway, suggesting complex biological behaviours in the coordination of metabolite biosynthesis and accumulation. The genomic dataset and analyses presented here lay the foundation for further research on this important medicinal plant.